Long-term immunogenicity after measles vaccine vs. wild infection: an Italian retrospective cohort study - Francesco Paolo Bianchi; Simona Mascipinto; Pasquale Stefanizzi; Sara De Nitto; Cinzia Germinario; Silvio Tafuri (Taylor & Francis Group, 2021)
The persistence of specific IgG after measles infection and after measles vaccination has not been sufficiently investigated. Current evidence suggests that immunity after the disease is life-long, whereas the response after two doses of measles-containing vaccine declines within 10-15 years. This study evaluated the proportion of individuals with detectable anti-measles IgG in two groups, those vaccinated with two doses of anti-MMR vaccine and those with a self-reported history of measles infection. Among the 611 students and residents who were tested, 94 (15%) had no detectable protective anti-measles IgG. This proportion was higher among vaccinated individuals (20%; GMT = 92.2) than among those with a self-reported history of measles (6%; GMT = 213.3; p < .0001). After one or two MMR vaccine booster doses, the overall seroconversion rate was 92%. An important proportion of people immunized for measles did not have a protective IgG titer in the years after vaccination, but among those who had a natural infection the rate was three-fold lower. This finding should be considered in the pre-elimination phase, given the resurgence of measles cases among individuals who after being vaccinated lost their circulating IgG after several years, especially if they failed to receive a natural booster.